2011
DOI: 10.1167/iovs.10-6008
|View full text |Cite
|
Sign up to set email alerts
|

Do Palisade Endings in Extraocular Muscles Arise from Neurons in the Motor Nuclei?

Abstract: These results confirm those of earlier studies and furthermore suggest that the somata of palisade endings are located close to the extraocular motor nuclei--in this case, probably within the C and S groups around the periphery of the oculomotor nucleus. The multiple en grappe endings have also been shown to arise from these cells groups, but it is not possible to distinguish different populations in these experiments.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
66
0
1

Year Published

2012
2012
2017
2017

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 48 publications
(72 citation statements)
references
References 58 publications
5
66
0
1
Order By: Relevance
“…[18][19][20] Combining anterograde tracer labeling and molecular analyses, we demonstrated that axons supplying palisade endings established several motor contacts alongside the muscle fibers in a manner equal to that of en grappe motor terminals on MIFs. 20 These findings strongly suggest that palisade endings arise from MIF motoneurons in the EOM motor nuclei although receptors for cholinergic transmission have not been found in palisade endings so far with the exception of rabbit and rat.…”
Section: Developmental Support For a Mif Motoneuronpalisade Ending Comentioning
confidence: 88%
“…[18][19][20] Combining anterograde tracer labeling and molecular analyses, we demonstrated that axons supplying palisade endings established several motor contacts alongside the muscle fibers in a manner equal to that of en grappe motor terminals on MIFs. 20 These findings strongly suggest that palisade endings arise from MIF motoneurons in the EOM motor nuclei although receptors for cholinergic transmission have not been found in palisade endings so far with the exception of rabbit and rat.…”
Section: Developmental Support For a Mif Motoneuronpalisade Ending Comentioning
confidence: 88%
“…Because these two sets of experiments were performed in different species with known differences in the eye proprioceptive system (e.g., extraocular muscle spindles are absent in the monkey but present in humans; Donaldson, 2000), interspecies differences could have been responsible for the apparent contradiction between their conclusions. Another possible source of discrepancy is the concern that in the experiment by Lewis et al (1998), despite the bilateral section of the trigeminal nerves, sufficient proprioceptive input could reach the CNS via the oculomotor nuclei, which have recently been suggested to receive sensory input from the pallisade endings (Lienbacher et al, 2011). The current experiment tested in the same subjects how visual localization is affected by both the conflict between the proprioceptive inflow and the efference copy (e.g., by comparing the baseline and the push condition) as well as by the reduction in the proprioceptive afference (e.g., by comparing the patient and the healthy group).…”
Section: Discussionmentioning
confidence: 99%
“…Specific eye movements and other oculomotor functions may hence receive different support from the respective neural circuits. Many aspects of this organisation are yet to be resolved (Lienbacher, Mustari, Ying, Büttner-Ennever, & Horn, 2011), but the concept of an infranuclear, independent motor control adds credence to other novel observations, such as the dual distal insertions of extraocular muscles (Demer, Miller, Poukens, Vinters, & Glasgow, 1995;Ruskell, Kjellevold Haugen, Bruenech, & van der Werf, 2005). The latter findings suggest that only global fibres are directly occupied with ocular rotation, while orbital fibres predominantly influence the muscle's direction of pull (Demer, 2006).…”
Section: Introductionmentioning
confidence: 81%
“…However, this rests on the assumption that the myotendinous nerve terminals are sensory in origin, a view which has been challenged (Lienbacher et al, 2011). Observations of nerve terminals with efferent features have led some authorities to promote that these structures form part of the conventional motor innervations of the MIFs (Blumer et al, 2009).…”
Section: Sensory Receptorsmentioning
confidence: 99%